Perlindungan Hak Asasi Anak Jalanan Dalam Bidang Pendidikan Menurut Hukum Nasional Dan Konvensi Internasional - Haling, Syamsul; Halim, Paisal; Badruddin, Syamsiah; Djanggih, Hardianto (UI Scholars Hub, 2018)
Street children however have become phenomena that demand the attention of all parties. The existence of this research raises the problem, namely, First, How the Behavior and Qualification Child Education Ham Violations Education, How Efforts and Protection of Rights of Street Children in The Field of Education. Method of Study is a juridical-normative method by examining national legislation and international conventions relating to the rights of children in the field of education. The results showe, a form of violation of the rights of street children in the field of education is an action neglected by the government and including the category of violence by omission that can be justified juridically to the government that there is obligation for the government to be held accountable in the area of law